2018
DOI: 10.1038/s41598-018-19404-z
|View full text |Cite
|
Sign up to set email alerts
|

Sudden sensory neural hearing loss is not predictive of myocardial infarction: A longitudinal follow-up study using a national sample cohort

Abstract: The aim of this study was to evaluate the risk of myocardial infarction (MI) in SSNHL subjects with differently matched control groups. The Korean Health Insurance Review and Assessment Service - National Sample Cohort recruited subjects from 2002 to 2013. We used two study designs. In study I, we matched 4,467 SSNHL participants with a control group (17,868 subjects with no history of SSNHL) based on demographic factors (age, sex, income, and region of residence) and medical history (diabetes, dyslipidemia, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 22 publications
0
23
0
Order By: Relevance
“…Given that the cochlea are primarily affected by the end‐arterial supply from the anterior inferior cerebellar artery, whether the pregnancy‐associated hypercoagulable state influences thrombotic arterial occlusion in the cochlea remains unknown. Using a large population‐based study, we recently reported no association between SSNHL and myocardial ischemia, even after excluding confounding factors, including systemic inflammatory mediators . Considering that specific etiologies of SSNHL, such as viral infection, ischemic insult, and autoimmunity, have been identified in only approximately 10% of patients, the risk of the ischemic insult that may precipitate SSNHL remains enigmatic.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Given that the cochlea are primarily affected by the end‐arterial supply from the anterior inferior cerebellar artery, whether the pregnancy‐associated hypercoagulable state influences thrombotic arterial occlusion in the cochlea remains unknown. Using a large population‐based study, we recently reported no association between SSNHL and myocardial ischemia, even after excluding confounding factors, including systemic inflammatory mediators . Considering that specific etiologies of SSNHL, such as viral infection, ischemic insult, and autoimmunity, have been identified in only approximately 10% of patients, the risk of the ischemic insult that may precipitate SSNHL remains enigmatic.…”
Section: Discussionmentioning
confidence: 99%
“…The reported global incidence of SSNHL varied from 5 to 20 per 100,000 individuals . In Korea, the annual incidence is approximately 10 per 100,000 individuals . The exact pathophysiology of SSNHL has not yet been clearly elucidated in most cases .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations